Nanna Rögnvaldardóttir: Icelandic Food and Cookery - Davidson, Alan (Petits Propos Culinaires, 2024)
Nanna Rögnvaldardóttir: Icelandic Food and Cookery: Hippocrene, New York, 2002: ISBN 0-7818-0878-2: 242 pp., h/b, 24.95.